Genre Features of the Educational Media Discourse in the Context of Information Ecology and Cyber Security - Olga V. Sergeeva; Marina R. Zheltukhina; Elena B. Ponomarenko (RUDN Journal of Language Studies, Semiotics and Semantics)
In the 21st century, the interdisciplinary research interest is increasingly aroused by the linguistic problem of realizing educational discourse, especially in the media space. Information ecology and cyber security make it possible to form the skill of making adequate educational, and managerial decisions in the field of education under the conditions of saturation with information, information noise in the digital environment. The purpose of the study is to identify the genre features of the educational media discourse in the context of information ecology and cyber security. A functional-genre analysis of the educational media discourse in the digital media space is carried out in the study. By applying a set of methods (descriptive method, content analysis, discursive analysis, linguosemiotic analysis, linguopragmatic analysis, functional-genre analysis, interpretive analysis), the genre media reflection of the regulation of society’s activities to achieve hygienic safety goals related to information is studied, which constitutes the scientific novelty of the study. The main genres of the educational media discourse that are significant for the development of genre theory have been identified, those are: analytical, popularizing, explanatory, didactic, regulating, recommendation, discussion, multimedia, case study genres. Their analyses allow conclude that an ecosystem comfortable for training students is formed due to compliance with the requirements of information ecology, information and Internet hygiene, ethics, cyber security, which are among the preventive trends and protective measures in the digital environment. The analysis of factual material emphasizes the importance of ensuring the safety of students as one of the key tasks of the modern educational process, considering the active influence of the media environment. It is established that media articles inform an addressee about the activities of preventive medicine and state sanitary and epidemiological services that are developing norms that reflect the safe organization of the work and educational process using information tools in the digital media space. Documents presented in various media genres determine the norms of lighting at different times of the day, the norms of noise parameters and work with electronic teaching aids and other acceptable conditions to ensure high-quality work without harm to health. The identified genre features of the educational media discourse in the context of information ecology and cyber security clearly demonstrate that the informational ecology is a promising direction for the study and development of the media discourse, incl. educational media discourse, based on the material of various linguistic cultures.